Dietary flavonoids may improve insulin resistance: NHANES, network pharmacological analyses and in vitro experiments - Xiaohui Sui; Yanhong Liu; Junde Zhao; Zuocheng Wang; Guiju Zhang (PLoS ONE, 2025)
Background Insulin resistance (IR) constitutes the pivotal pathological link underlying numerous metabolic diseases and represents a paramount global health challenge. Flavonoids have demonstrated beneficial effects on diseases such as cancer and hypertension through their anti-inflammatory and antioxidant activities. However, the relationship between dietary flavonoid intake and IR prevalence remains unclear. Methods The cross-sectional study utilized population data from the 2007–2010 and 2017–2018 National Health and Nutrition Examination Surveys (NHANES). IR assessment employed the metabolic score for insulin resistance (METS-IR). The relationship between dietary flavonoid intake and IR underwent analysis by weighted generalized linear regression and weighted restricted cubic splines (RCS). The mechanism of flavonoid action on IR was studied by network pharmacology and molecular docking, and verified in vitro. Since the free form compound did not exist, we conducted subsequent experiments using the stable salt form Cyanidin Chloride. Results Our findings revealed statistically significant negative associations between Anthocyanidins (P < 0.0001) and Flavanones (P < 0.001) and IR. Meanwhile, relative to the minimal concentration group, the low concentration group (β = −1.39, P = 0.02) and the moderate concentration group (β = −2.84, P = 0.001) of total flavonol intake had the potential to reduce METS-IR. RCS showed that total flavonoids, Anthocyanidins, Isoflavone, Flavan-3-ols, Flavanones, Flavones and Flavonols had a nonlinear correlation with IR. In vitro experimentation corroborated these findings: after adding anthocyanidins and hesperidin supplementation, glucose uptake was significantly restored in the IR group, ameliorating IR. Conclusion Our study highlights the importance of appropriately increasing dietary flavonoid intake when improving IR.